Polysulfide and persulfide-mediated activation of the PERK-eIF2α-ATF4 pathway increases Sestrin2 expression and reduces methylglyoxal toxicity - Shin Koike; Hideo Kimura; Yuki Ogasawara (Redox Biology)
Unfolded protein response (UPR) is activated in cells under endoplasmic reticulum (ER) stress. One sensor protein involved in this response is PERK, which is activated through its redox-dependent oligomerization. Prolonged UPR activation is associated with the development and progression of various diseases, making it essential to understanding the redox regulation of PERK. Sulfane sulfur, such as polysulfides and persulfides, can modify the cysteine residues and regulate the function of various proteins. However, the regulatory mechanism and physiological effects of sulfane sulfur on the PERK–eIF2α–ATF4 pathway remain poorly understood. This study focuses on the persulfidation of PERK to elucidate the effects of polysulfides on the PERK–eIF2α–ATF4 pathway and investigate its cytoprotective mechanism. Here, we demonstrated that polysulfide treatment promoted the oligomerization of PERK and PTP1B in neuronal cells using western blotting under nonreducing conditions. We also observed that l-cysteine, a biological source of sulfane sulfur, promoted the oligomerization of PERK and the knockdown of CBS and 3-MST, two sulfane sulfur-producing enzymes, and reduced PERK oligomerization induced by l-cysteine treatment. Furthermore, the band shift assay and LC–MS/MS studies revealed that polysulfides and persulfides induce PTP1B and PERK persulfidation. Additionally, polysulfides promoted eIF2α phosphorylation and ATF4 accumulation in the nucleus, suggesting that polysulfides activate the PERK–eIF2α–ATF4 pathway in neuronal cells. Moreover, polysulfides protected neuronal cells from methylglyoxal-induced toxicity, and this protective effect was reduced when the expression of Sestrin2, regulated by ATF4 activity, was suppressed. This study identified a novel mechanism for the activation of the PERK–eIF2α–ATF4 pathway through persulfidation by polysulfides and persulfides. Interestingly, activation of this pathway overcame the toxicity of methylglyoxal in dependence on Sestrin2 expression. These findings deepen our understanding of neuronal diseases involving ER stress and UPR disturbance and may inspire new therapeutic strategies.